2016
DOI: 10.1080/14623943.2015.1123688
|View full text |Cite
|
Sign up to set email alerts
|

An embodied perspective on judgements of written reflective practice for professional development in Higher Education

Abstract: This paper gives an embodied perspective on the use of judgements of reflective practice and reflective writing for professional development in Higher Education.Programmes for professional development in Higher Education and recognition processes for academics have become prevalent in the UK and internationally.These programmes and processes often assume, implicitly or explicitly, development or evidencing as a 'reflective practitioner' through pieces of reflective writing which is then judged against competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 63 publications
1
23
0
4
Order By: Relevance
“…Latta and Buck (2007) found that there are potential risks and opportunities in a collaborative self-study, yet it is a valuable vehicle for professional development. Reflection was a major component of the CITE initiative, as Leigh (2016) reported, that reflexivity implies individuals take time to reflect on and analyse their actions and awareness of themselves, and then use those insights to improve their practice.…”
Section: Methodsmentioning
confidence: 99%
“…Latta and Buck (2007) found that there are potential risks and opportunities in a collaborative self-study, yet it is a valuable vehicle for professional development. Reflection was a major component of the CITE initiative, as Leigh (2016) reported, that reflexivity implies individuals take time to reflect on and analyse their actions and awareness of themselves, and then use those insights to improve their practice.…”
Section: Methodsmentioning
confidence: 99%
“…Integration of scholarship and professional activities with students and colleagues is an important aspect of academic teaching. The authors have observed over the last 5 years that many teachers are successful when improving their teaching and learning opportunities for students but lacking the time or commitment to customise their body of evidence of their own practice for a particular purpose such as academic promotion effectively [14].…”
Section: Scaffolding Critical Reflectionmentioning
confidence: 99%
“…It is expected that academics studying for this award will develop the ability to focus inwardly on their own practice as well as outwardly gauge the impact of changes they make to learning and teaching in their subject discipline [14].…”
Section: Scaffolding Critical Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflective practice and reflective writing have become intrinsic within professional practice education and programmes nationally and internationally [13]. Reflective writing is one established method for teaching students to effectively elicit, interpret, and translate their stories [14].…”
Section: The Learning Outcomementioning
confidence: 99%